Advances and challenges in gene therapy strategies for pediatric cancer: a comprehensive update - Moaveni, Amir Kian; Amiri, Maryam; Shademan, Behrouz; Farhadi, Arezoo; Behroozi, Javad; Nourazarian, Alireza (Frontiers in Molecular Biosciences, 2024)
Pediatric cancers represent a tragic but also promising area for gene therapy. Although conventional treatments have improved survival rates, there is still a need for targeted and less toxic interventions. This article critically analyzes recent advances in gene therapy for pediatric malignancies and discusses the challenges that remain. We explore the innovative vectors and delivery systems that have emerged, such as adeno-associated viruses and non-viral platforms, which show promise in addressing the unique pathophysiology of pediatric tumors. Specifically, we examine the field of chimeric antigen receptor (CAR) T-cell therapies and their adaptation for solid tumors, which historically have been more challenging to treat than hematologic malignancies. We also discuss the genetic and epigenetic complexities inherent to pediatric cancers, such as tumor heterogeneity and the dynamic tumor microenvironment, which pose significant hurdles for gene therapy. Ethical considerations specific to pediatric populations, including consent and long-term follow-up, are also analyzed. Additionally, we scrutinize the translation of research from preclinical models that often fail to mimic pediatric cancer biology to the regulatory landscapes that can either support or hinder innovation. In summary, this article provides an up-to-date overview of gene therapy in pediatric oncology, highlighting both the rapid scientific progress and the substantial obstacles that need to be addressed. Through this lens, we propose a roadmap for future research that prioritizes the safety, efficacy, and complex ethical considerations involved in treating pediatric patients. Our ultimate goal is to move from incremental advancements to transformative therapies.